Cell Death Is Not Sufficient for the Restriction of Potato Virus Y Spread in Hypersensitive Response-Conferred Resistance in Potato - Lukan, Tjaša; Baebler, Špela; Pompe-Novak, Maruša; Guček, Katja; Zagorščak, Maja; Coll, Anna; Gruden, Kristina (Frontiers in Plant Science, 2018)
Hypersensitive response (HR)-conferred resistance to viral infection restricts the virus spread and is accompanied by the induction of cell death, manifested as the formation of necrotic lesions. While it is known that salicylic acid is the key component in the orchestration of the events restricting viral spread in HR, the exact function of the cell death in resistance is still unknown. We show that potato virus Y (PVY) can be detected outside the cell death zone in Ny-1-mediated HR in potato plants (cv. Rywal), observed as individual infected cells or small clusters of infected cells outside the cell death zone. By exploiting the features of temperature dependent Ny-1-mediated resistance, we confirmed that the cells at the border of the cell death zone are alive and harbor viable PVY that is able to reinitiate infection. To get additional insights into this phenomenon we further studied the dynamics of both cell death zone expansion and occurrence of viral infected cell islands outside it. We compared the response of Rywal plants to their transgenic counterparts, impaired in SA accumulation (NahG-Rywal), where the lesions occur but the spread of the virus is not restricted. We show that the virus is detected outside the cell death zone in all lesion developmental stages of HR lesions. We also measured the dynamics of lesions expansion in both genotypes. We show that while rapid lesion expansion is observed in SA-depleted plants, virus spread is even faster. On the other hand the majority of analysed lesions slowly expand also in HR-conferred resistance opening the possibility that the infected cells are eventually engulfed by cell death zone. Taken altogether, we suggest that the HR cell death is separated from the resistance mechanisms which lead to PVY restriction in Ny-1 genetic background. We propose that HR should be regarded as a process where the dynamics of events is crucial for effectiveness of viral arrest albeit the exact mechanism conferring this resistance remains unknown.